What Are Schools Looking for in New, Inclusive Teachers? - Sokal, Laura (McGill Journal of Education / Revue des sciences de l'éducation de McGill)

(untitled) (Faculty of Education, McGill University, 2012)
Focus groups were conducted in four school divisions in central Canada in order to determine whether inclusive educators in schools could identify the knowledge base, skills set, and attitudes desirable in new inclusive teachers. Participants failed to identify an essential knowledge base for inclusive educators. Findings indicated that a focus on skills and attitudes was viewed as desirable, specifically skills related to flexibility, inter-dependence, communication. Participants also valued attitudes related to willingness on the part of new teachers to seek learning opportunities and accept help from other team members.